2016
DOI: 10.1007/s00402-016-2551-4
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison between the modified rolling-hitch and the modified finger-trap suture techniques

Abstract: This study showed that both suture methods appear to be biomechanically effective in a porcine tendon model. However, the single-knot grasping technique (MRH) provided superior biomechanical properties compared with the MFT technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…In a biomechanical study, Hong et al [10] proposed the modified rolling hitch to be an attractive technique for suture-tendon constructs because it had similar elongation after cyclic loading and load to failure as the modified Prusik knot and Wittstein suture loop; additionally, Krappinger et al [12] found that the modified Prusik knot had smaller force-induced displacements than the whipstitch technique. However, whereas Camarda et al [2] reported that the modified rolling hitch provided better biomechanical properties than the modified finger-trap technique, Su et al [15] reported that the modified finger-trap featured superior biomechanical properties to the Krackow stitch. Although two prior studies [2,10] did not biomechanically compare the modified rolling hitch and the commonly used needled techniques directly, according to the above previous findings, we could infer that the modified rolling hitch may have comparable or better biomechanical properties compared with the whipstitch or Krackow stitch.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a biomechanical study, Hong et al [10] proposed the modified rolling hitch to be an attractive technique for suture-tendon constructs because it had similar elongation after cyclic loading and load to failure as the modified Prusik knot and Wittstein suture loop; additionally, Krappinger et al [12] found that the modified Prusik knot had smaller force-induced displacements than the whipstitch technique. However, whereas Camarda et al [2] reported that the modified rolling hitch provided better biomechanical properties than the modified finger-trap technique, Su et al [15] reported that the modified finger-trap featured superior biomechanical properties to the Krackow stitch. Although two prior studies [2,10] did not biomechanically compare the modified rolling hitch and the commonly used needled techniques directly, according to the above previous findings, we could infer that the modified rolling hitch may have comparable or better biomechanical properties compared with the whipstitch or Krackow stitch.…”
Section: Discussionmentioning
confidence: 99%
“…Although some biomechanical studies have suggested the modified rolling hitch to be effective in holding tendon grafts [2,10], to our knowledge no study has compared the traditional suture techniques with the modified rolling hitch or the rolling hitch. We biomechanically evaluated the rolling hitch, modified rolling hitch, and Krackow stitch for preparing tendon grafts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations